Current Heavy Alcohol Consumption is Associated with Greater Cognitive Impairment in Older Adults. (22nd September 2016) - Woods, Adam J.; Porges, Eric C.; Bryant, Vaughn E.; Seider, Talia; Gongvatana, Assawin; Kahler, Christopher W.; de la Monte, Suzanne; Monti, Peter M.; Cohen, Ronald A.
Abstract : Background: The acute consumption of excessive quantities of alcohol causes well‐recognized neurophysiological and cognitive alterations. As people reach advanced age, they are more prone to cognitive decline. To date, the interaction of current heavy alcohol (ethanol [EtOH]) consumption and aging remains unclear. This study tested the hypothesis that negative consequences of current heavy alcohol consumption on neurocognitive function are worse with advanced age. Further, we evaluated the relations between lifetime history of alcohol dependence and neurocognitive function Methods: Sixty‐six participants underwent a comprehensive neurocognitive battery. Current heavy EtOH drinkers were classified using National Institute on Alcohol Abuse and Alcoholism criteria (EtOH heavy, n  = 21) based on the Timeline follow‐back and a structured clinical interview and compared to nondrinkers, and moderate drinkers (EtOH low, n  = 45). Of the total population, 53.3% had a lifetime history of alcohol dependence. Neurocognitive data were grouped and analyzed relative to global and domain scores assessing: global cognitive function, attention/executive function, learning, memory, motor function, verbal function, and speed of processing. Results: Heavy current EtOH consumption in older adults was associated with poorer global cognitive function, learning, memory, and motor function ( p s < 0.05). Furthermore, lifetime history of alcohol dependence was associated with poorer function in the same neurocognitive domains, in addition to the attention/executive domain, irrespective of age ( p s < 0.05). Conclusions: These data suggest that while heavy current alcohol consumption is associated with significant impairment in a number of neurocognitive domains, history of alcohol dependence, even in the absence of heavy current alcohol use, is associated with lasting negative consequences for neurocognitive function. Abstract : As we age, our susceptibility to negative consequences of heavy alcohol consumption for thinking, memory, and motor skills appears to increase. While there were no significant cognitive differences evident in younger adults that did and did not drink heavily, current heavy alcohol consumption in older adults was associated with significantly poorer cognitive function in learning, memory, and speeded motor function, as well as a global marker of cognition.